A Nation Forged in War : How World War II Taught Americans to Get Along - Bruscino, Thomas A. (Book collections on Project MUSE., 2010)
World War II shaped the United States in profound ways, and this new book--the first in the Legacies of War series--explores one of the most significant changes it fostered: a dramatic increase in ethnic and religious tolerance. A Nation Forged in War is the first full-length study of how large-scale mobilization during the Second World War helped to dissolve long-standing differences among white soldiers of widely divergent backgrounds. Never before or since have so many Americans served in the armed forces at one time: more than 15 million donned uniforms in the period from 1941 to 19.